(untitled) (Revista Científica Integrada, 2023)
Objective: To report the diagnosis of mastitis in a man by means of an ultrasound examination. Methods: This is a case report, based on the review of the medical records of a radiology medical center, collected in May 2022, in Santos, São Paulo. For this case, photographic records of the diagnostic method were used. Furthermore, a narrative review was performed to support the findings. Results: Male patient, 63 years old, complaining of pain in the left breast for two days, being treated for an ischemic stroke with ischemic thrombolysis. On physical examination, she presented periareolar hyperemia in the left breast, with hardening and pain on palpation. Ultrasonography of the left breast showed collection with increased vascular flow on color Doppler study in the stromal tissue of the retroareolar region, characterizing gynecomastia with associated mastitis. Conclusions: Gynecomastia associated with mastitis is rare in men. Diagnosis is based on clinical history and imaging tests such as ultrasonography.